Kegunaan hasil informasi penelitian BP3K bagi pengambilan keputusan kebijaksanaan di lingkungan Departemen Pendidikan dan Kebudayaan - Dahliani, Yenny (Seri penataran penelitian pendidikan, 1981)
Results of a study within the Dept. of Education and Culture on utilizing information supplied by the Office of Educational and Cultural Research and Development for making decisions and policies.